TECHNICAL GUIDANCE HOUSEHOLD ORGANIC WASTE FERTILIZER PRODUCTION TO SUPPORT URBAN FARMING ON ANTHROPOGENIC LAND FOR THE DASAWISMA GROUPS - La Ode Rustam; Darwis Darwis; Rian Arini; Abdi Abdi (LPPM Universitas Flores, 2026)
The continuous availability of household waste represents an adaptive resource potential for organic fertilizer production. The availability of organic fertilizer is highly crucial for optimizing crop cultivation on anthropogenic land (degraded land caused by Type C quarrying) surrounding community residential yards. This Internal Community Partnership Program (PKMI) aimed to enhance partners' understanding of managing degraded land to restore its productivity, and to improve their knowledge regarding the independent conversion of household waste into ready-to-use organic fertilizer. The target partners of this program were the Gunung Sakura and Bunga Sakura Dasawisma Groups in Mandonga Village, Kendari City. The implementation methods comprised program socialization, technical guidance (training) on decomposition engineering utilizing EM4 bioactivator and rice bran through the field capacity method, and periodic monitoring and evaluation. The evaluation results demonstrated that the PKMI program was successfully executed, achieving a program outcomes attainment rate of 80.0%, which exceeded the success indicator target (>75%). Post-activity, the Dasawisma groups achieved a 100% level of comprehension in identifying potential organic waste components. Furthermore, they acquired technical knowledge and skills (100% in the problem-solving aspect) to independently produce solid organic fertilizer within a 14–21 day fermentation period. The generated fertilizer product serves as an effective solution for restoring backyard soil fertility and supporting the sustainability of urban farming.